Larangan Perkawinan Beda Agama di Indonesia: Tinjauan Konstitusional dan Prinsip Kebebasan Beragama - Mohamad Iksan; Yusuf Hidayatulloh; Imam Faturrahman; Haikal Habinurrohman; Bibin Bunyamin (SIYASI: Jurnal Trias Politica, 2026)
This study aims to analyze the constitutional standing of the prohibition on interfaith marriage within Indonesia's national legal system, examine the normative tension between the guarantee of religious freedom and the permissible limitations under Article 28J paragraph (2) of the 1945 Constitution of the Republic of Indonesia, and identify its legal implications for legal certainty and family rights. The study employs a normative-juridical method combined with a socio-legal approach through a systematic review of legislation, Constitutional Court decisions, and reputable legal literature. The findings reveal that the prohibition on interfaith marriage holds a firm constitutional legitimacy, consistently affirmed by the Constitutional Court through Decisions Number 68/PUU-XII/2014, Number 24/PUU-XX/2022, and Number 146/PUU-XX/2024, which establish religious law as a constitutive requirement for the validity of marriage within the framework of the Pancasila state. Nevertheless, the absolute prohibition without any alternative civil protection instrument produces a disproportionate impact on children's rights and family legal certainty. This study recommends the establishment of a tertium genus legal framework that separates the domain of religious validity from the domain of civil rights protection, in order to ensure a balance between the constitutional value of Belief in One God and the state's obligation to safeguard the fundamental rights of all citizens.